Mutation screening of NOS1AP gene in a large sample of psychiatric patients and controls - Nygren Gudrun; Schuroff Franck; Jamain Stéphane; Chaste Pauline; Anckarsäter Henrik; Scheid Isabelle; Betancur Catalina; Delorme Richard; Herbrecht Evelyn; Dumaine Anne; Mouren Marie; Råstam Maria; et al. (BMC, 2010)
Abstract Background The gene encoding carboxyl-terminal PDZ ligand of neuronal nitric oxide synthase (NOS1AP) is located on chromosome 1q23.3, a candidate region for schizophrenia, autism spectrum disorders (ASD) and obsessive-compulsive disorder (OCD). Previous genetic and functional studies explored the role of NOS1AP in these psychiatric conditions, but only a limited number explored the sequence variability of NOS1AP. Methods We analyzed the coding sequence of NOS1AP in a large population (n = 280), including patients with schizophrenia (n = 72), ASD (n = 81) or OCD (n = 34), and in healthy volunteers controlled for the absence of personal or familial history of psychiatric disorders (n = 93). Results Two non-synonymous variations, V37I and D423N were identified in two families, one with two siblings with OCD and the other with two brothers with ASD. These rare variations apparently segregate with the presence of psychiatric conditions. Conclusions Coding variations of NOS1AP are relatively rare in patients and controls. Nevertheless, we report the first non-synonymous variations within the human NOS1AP gene that warrant further genetic and functional investigations to ascertain their roles in the susceptibility to psychiatric disorders.